TRANSLATING A SUNDANESE NOVELETTE: PROBLEMS AND CHALLENGES - Rika Novia Dewi; Dedy Setiawan (Jurnal Bahasa Inggris Terapan, 2017)
Translation  initially is  transferring  an  idea  from  one  into another language. The idea translated is in a form of concept or messages which the writer puts in his/her writing. Translating a literary work is more than just trsnfering concept or story flow, arising from the art work, it should also be able to illustrate the message which can be culturally or literally impacted. This article describes an experience of the wrirters when translating a Sundanese novellete which is full of cultural aspect which is specific to a particular ethnic group in Indonesia. It also elaborates the translation process, the method used and discussion translating cultural words. Keywords: Sundanese, culture, translation process, cultural words